Board Size and Corporate Risk: Evidence from China. Issue 3 (2nd July 2016) - Haider, Junaid; Fang, Hong-Xing
ABSTRACT: The purpose of this study is to investigate the negative relationship between board size and corporate risk taking in a unique market and institutional environment of China. The authors used a comprehensive sample of 1, 502 Chinese listed firms, over a sample period of 2008 to 2013. Empirical findings show that despite the uniqueness of Chinese corporate governance features, board size is negatively associated with corporate risk taking. However, the economic impact of change in board size is much smaller than other developed market context, highlighting the exclusive features of Chinese boards and market.